2022
DOI: 10.1002/ajmg.a.63088
|View full text |Cite
|
Sign up to set email alerts
|

Cardiometabolic profiles in children and adults with overweight and obesity and down syndrome

Abstract: Individuals with Down syndrome (DS) are at increased risk for being overweight/obese, but the associated cardiometabolic risk (CR) is not clear. Cross‐sectional anthropometric and clinical laboratory data from a multi‐site, international cohort of individuals with DS were analyzed to determine cardiometabolic risk by reporting observed distributions of cardiometabolic biomarkers in overweight/obese individuals with DS throughout the lifespan. Descriptive statistics and regression analyses by age categories det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Various clinical factors may account for the observed differences in 25(OH)D levels within our cohort with DS. Higher BMI is more common in individuals with DS [ 46 , 47 ], as was found in our study and was associated with lower levels of 25(OH)D among individuals with DS. Higher BMI is associated with increased body fat, which can also sequester vitamin D, which may provide an explanation for this finding [ 48 , 49 ].…”
Section: Discussionsupporting
confidence: 84%
“…Various clinical factors may account for the observed differences in 25(OH)D levels within our cohort with DS. Higher BMI is more common in individuals with DS [ 46 , 47 ], as was found in our study and was associated with lower levels of 25(OH)D among individuals with DS. Higher BMI is associated with increased body fat, which can also sequester vitamin D, which may provide an explanation for this finding [ 48 , 49 ].…”
Section: Discussionsupporting
confidence: 84%
“…The prevalence of being overweight and/or obese among adults with DS ranges from 23% to 70% 19 . Other studies showed an obesity prevalence rate of 49% among DS youth, compared with 39% in the general youth population, and in a multicenter study, 94% of adults were found to have obesity 20,21 . Risk factors for obesity in this population include hypothyroidism, hypotonia, a lower resting metabolic rate, poor dietary habits, and insufficient physical activity 22 .…”
Section: Common Problems Encountered In Adults With Dsmentioning
confidence: 91%
“…19 Other studies showed an obesity prevalence rate of 49% among DS youth, compared with 39% in the general youth population, and in a multicenter study, 94% of adults were found to have obesity. 20,21 Risk factors for obesity in this population include hypothyroidism, hypotonia, a lower resting metabolic rate, poor dietary habits, and insufficient physical activity. 22 The current screening recommendations to address obesity in adults with DS entail an annual evaluation of body mass index at the primary care setting.…”
Section: Obesitymentioning
confidence: 99%
“…Their genetic profile may also impact the deleterious interactions of some of the traditional risk factors, as demonstrated by a recent study that reported that being overweight/obese did not correlate with worse cardiovascular biomarkers in individuals with DS (Oreskovic et al . 2022).…”
Section: Introductionmentioning
confidence: 99%